Self-Differentiation and its Relationship with the Selection Criteria of the Life Partner among Yarmouk University Students - Al-Khaldi, Ghaida’a Mahmoud; Momani, Fawwaz Ayoub (Jordan Journal of Social Sciences, 2024)
The study aimed to explore self-differentiation and its relationship with the selection criteria of the life partner among students at Yarmouk University. The sample consisted of 813 male and female students. The self-differentiation scale and the partner selection criteria scale were used after their psychometric properties were confirmed. The results indicated that levels of all dimensions of self-differentiation were moderate except for the aspect of "self-position" which was found to be at a high level. The results also found statistically significant differences concerning all dimensions of self-differentiation related to gender, except for the emotional cutoff dimension. Moreover, the results found statistically significant differences with respect to all dimensions of self-differentiation related to the educational level. No statistically significant differences were found related to the place of residence or birth order. The results revealed that all partner selection criteria were high, except for the "psychological criterion" which was found to be exceptionally high. Statistically significant differences in all criteria were linked to gender. Additionally, there are statistically significant differences of economic and psychological criteria, which were associated with the educational level. However, no statistically significant differences related to birth order were found for all criteria. Similarly, no differences were attributed to the socio-cultural and economic criteria due to the place of residence. However, differences were found in the psychological and physical criteria attributed to the place of residence. The results also revealed a statistically positive correlation (weak, very weak) between self-differentiation dimensions and the partner selection criteria. Based on these findings, several recommendations were drawn, emphasizing the importance of educating young individuals about the selection criteria of the life partner.